2006
DOI: 10.1021/bi061311a
|View full text |Cite
|
Sign up to set email alerts
|

A Single γ-Carboxyglutamic Acid Residue in a Novel Cysteine-Rich Secretory Protein without Propeptide,

Abstract: Gamma-glutamyl carboxylase catalyzes the modification of specific glutamyl residues to gamma-carboxyglutamyl (Gla) residues in precursor proteins that possess the appropriate gamma-carboxylation recognition signal within the propeptide region. We describe the immunopurification and first biochemical characterization of an invertebrate high molecular weight Gla-containing protein with homologues in mammals. The protein, named GlaCrisp, was isolated from the venom of the marine cone snail Conus marmoreus. GlaCri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Most hypothesized roles of Gla residues in the many proteins involve coordination of calcium. 41,43,44 In contrast, Gla36 in protein S is not predicted to coordinate calcium 19 (Figure 5B), neither is it involved in phospholipid binding of protein S. In a model of Gla-TSR-EGF1 domains of protein S, 19 Gla36 lies outside of the -loop and is predicted to point away from the phospholipid membrane ( Figure 5B). Collectively, this suggests that the ␥-carboxylation of Glu36 is essential for protein S function and is involved in the interactions through which protein S enhances APC function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most hypothesized roles of Gla residues in the many proteins involve coordination of calcium. 41,43,44 In contrast, Gla36 in protein S is not predicted to coordinate calcium 19 (Figure 5B), neither is it involved in phospholipid binding of protein S. In a model of Gla-TSR-EGF1 domains of protein S, 19 Gla36 lies outside of the -loop and is predicted to point away from the phospholipid membrane ( Figure 5B). Collectively, this suggests that the ␥-carboxylation of Glu36 is essential for protein S function and is involved in the interactions through which protein S enhances APC function.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, Gla residues have also been identified in peptides from invertebrates, 41,42 which are thought to have evolved before blood coagulation. Most hypothesized roles of Gla residues in the many proteins involve coordination of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of testis-specific protein 1 (Tpx-1, CRISP-2; Hardy et al, 1988;Kasahara et al, 1989) and specific granule protein of 28 kDa (SGP28, CRISP-3; Haendler et al, 1993;Kjeldsen et al, 1996), four CRISPs (CRISP-1-CRISP-4) have now been identified in mammalian tissues. Furthermore, it has also been shown that CRISPs are widely distributed in non-mammalian species, including Xenopus (Olson et al, 2001), Caenorhabditis elegans (Ookuma et al, 2003) and the venoms of lizards (Nobile et al, 1994(Nobile et al, , 1996Morrissette et al, 1995), cone snails (Milne et al, 2003;Hansson et al, 2006) and snakes (Yamazaki & Morita, 2004, 2007. Although clear evidence for either function or target molecules is lacking for most of the CRISPs, including endogenous CRISPs, recent evidence has emerged suggesting that some exogenous CRISPs derived from venomous snakes may function as ion-channel blockers (Nobile et al, 1994(Nobile et al, , 1996Brown et al, 1999Brown et al, , 2003Yamazaki, Brown et al, 2002;Yamazaki, Koike et al, 2002;Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Given the generalized expression of the ␥-carboxylase in most or all tissues, it is likely that a number of other Gla-containing proteins with specialized functions remain to be identified, including additional members of a recently characterized class of proteins lacking a conventional ␥-carboxylase recognition site. 24 The ␥-carboxylase requires reduced vitamin K as an obligate cofactor. The oral anticoagulant warfarin functions by inhibiting vitamin K epoxide reductase (VKOR) and thereby blocking the regeneration of active reduced vitamin K. 2 The VKOR gene has recently been cloned and shown to encode a small transmembrane protein localized to the ER.…”
Section: Introductionmentioning
confidence: 99%